DEVELOPMENT AND COMPLEXIZATION OF LATE SOCIETY OF THE CENTRAL COAST: THE CASE OF YCHSMA - Vallejo Berrios, Francisco (2008)
This research study presents a general review of the Peruvian Central Coast during the Intermediate Late Period based on new archaeological evidence and current studies. We intend to establish the factors of change in the Ychsma society. To do this, we discuss the concepts of culture, space, style and ceramic workshops. Finally, a preliminary identification takes into account tables of climatic oscillation and association with the evolution of societies during the Intermediate Late Period and are used as evidence to interpret these complex change.